2019
DOI: 10.1016/j.jclepro.2019.118249
|View full text |Cite
|
Sign up to set email alerts
|

Recycling marble wastes and Jarosite wastes into sustainable hybrid composite materials and validation through Response Surface Methodology

Abstract: During marble processing such as cutting, polishing and grinding, a considerable amount of fine residues refereed as marble processing rejects (MPRs) are produced and have become a serious environmental issue. So the current study deals with the conversion of MPRs into hybrid ceramic composite bricks (CCB) with Jarosite waste in a clay matrix

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
18
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 38 publications
(18 citation statements)
references
References 28 publications
0
18
0
Order By: Relevance
“…About 200 million tons of marble waste by marble processing industries, as a waste powder or sludge, has been produced worldwide. About 16 million tons of this waste has been created in India alone annually [ 5 , 6 , 7 , 8 ]. These marble processing industries involve mines and processing units for manufacturing tiles, blocks, decorative articles, waste disposal areas, and other activities [ 9 , 10 ].…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…About 200 million tons of marble waste by marble processing industries, as a waste powder or sludge, has been produced worldwide. About 16 million tons of this waste has been created in India alone annually [ 5 , 6 , 7 , 8 ]. These marble processing industries involve mines and processing units for manufacturing tiles, blocks, decorative articles, waste disposal areas, and other activities [ 9 , 10 ].…”
Section: Introductionmentioning
confidence: 99%
“…These marble processing industries involve mines and processing units for manufacturing tiles, blocks, decorative articles, waste disposal areas, and other activities [ 9 , 10 ]. Proper handling and management of marble wastes are necessary to protect the environment from the soil, water, and air contamination [ 6 , 11 ].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Rotatability is a reasonable basis for the selection of a response surface design [10]. The response surface methodology (RSM) with employment of Taguchi's orthogonal arrays, central composite design, regression models and so on, have shown significant improvements in process optimization [11][12][13].…”
Section: Introductionmentioning
confidence: 99%
“…From the literature review [1][2][3][4][5][6][7][8][9][10][11][12][13], it was found that some of the authors have reported the structural and thermal performance of various brake discs. Since, the structural performance of ventilated brake discs is a function of disc geometry and material, a comprehensive study on optimal combination of geometric parameters needs to be carried out.…”
Section: Introductionmentioning
confidence: 99%